Concurrent Validity and Reliability of Retrospective Scoring of the Pediatric NIH Stroke Scale - Beslow, Lauren A. (2011)
BACKGROUND AND PURPOSE: The Pediatric National Institutes of Health Stroke Scale (PedNIHSS), an adaptation of the adult NIH Stroke Scale, is a quantitative measure of stroke severity shown to be reliable when scored prospectively. The ability to calculate the PedNIHSS score retrospectively would be invaluable in the conduct of observational pediatric stroke studies. The study objective was to assess the concurrent validity and reliability of estimating the PedNIHSS score retrospectively from medical records. METHODS: Neurological examinations from medical records of 75 children enrolled in a prospective PedNIHSS validation study were photocopied. Four neurologists of varying training levels blinded to the prospective PedNIHSS scores reviewed the records and retrospectively assigned PedNIHSS scores. Retrospective scores were compared among raters and to the prospective scores. RESULTS: Total retrospective PedNIHSS scores correlated highly with total prospective scores (R(2)=0.76). Interrater reliability for the total scores was “excellent” (intraclass correlation coefficient of 0.95, 95% confidence interval 0.94–0.97). Interrater reliability for individual test items was “substantial” or “excellent” for 14 of 15 items. CONCLUSIONS: The PedNIHSS score can be scored retrospectively from medical records with a high degree of concurrent validity and reliability. This tool can be used to improve the quality of retrospective pediatric stroke studies.